Co-Production of Cellulase and Xylanase Enzymes By Thermophilic Bacillus subtilis 276NS - Ali, Safaa M.; Omar, Sanaa H.; Soliman, Nadia A. (International Journal of Biotechnology for Wellness Industries, 2013)
Co-production of thermostable extracellular cellulase and xylanase was investigated using bacterial soil isolate. To evaluate the effect of culture conditions on the c-oproduction of both enzymes by Bacillus subtilis 276NS (GenBank accession number JF801740), a Plackett-Burman fractional factorial design was applied. Among the tested variables, yeast extract, sucrose and incubation time were the most significant variables increased cellulase and xylanase productions. Both of xylan and CMC (Carboxymethyl Cellulose) induced the xylanse enzyme production. A near-optimum medium formulation was obtained which increased the cellulase and xylanase enzymes 5.7- and 1.08 –fold higher than the yield obtained with the basal medium, respectively. Thereafter, the response surface methodology was adopted to acquire the best process conditions among the selected variables (xylan, CMC and Yeast Extract (YE)) required for improving xylanase yield. The optimal combinations of the major medium constituents for xylanase production evaluated using non-linear optimization algorithm of EXCEL-solver, was as follows (g/L): D-sucrose, 10; xylan, 10.367, CMC, 10.535; (NH4)2 SO4, 1.0; YE, 1.71; Tween-80, 0.4 and FeSO4, 0.25 mg/L, at pH 8.0, temperature 35◦C and incubation time 24h under shaking. The predicted optimum thermostable xylanase activity was 360 U/ml, which was around 4-times the activity with the basal medium.